The Influence of Financial Literacy and Cashless Behavior on the Financial Management Behavior of Generation Z in Cirebon City - Khansa, Selma; Parlina, Nurhana Dhea; Agustina, Agustina (Asian Journal of Management Analytics, 2026)
This research examines how financial literacy and cashless transaction habits influence the way Generation Z in Cirebon City handles their finances.The development of digital financial technologies has significantly transformed transaction patterns from cash-based to digital systems, which demands better financial management capabilities, particularly among young individuals. A quantitative method with an associative approach was applied in this study, utilizing Data analysis using Structural Equation Modeling–Partial Least Squares (SEM-PLS). Respondents from Generation Z who actively utilise non-cash payment methods were given questionnaires to complete in order to gather data. The results show that financial management behaviour is significantly improved by financial literacy. In a similar vein, using cashless payment methods makes a substantial and positive contribution. A significant amount of the variation in respondents' financial management practices can be explained by both factors taken together.